Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Hello I would like to know what is the generic form to calculate a telescopic series.

http://www.dummies.com/how-to/content/how-to-analyze-a-telescoping-series.html

here uses a sum that startes at $n=1$, but what if it started at $n=2$ or $n=3$?

the $n$ index has any influence over the sum? I think yes, but no one explains this.. my series is:

$$\sum_{n=1}^\infty\frac{4}{(n+1)(n+2)}$$

how do I solve this really step by step for new people to those series

share|improve this question
2  
If you give us a particular sum, and tell us if how you want us to tweak it, then we might find it easier to write an answer. –  user21436 Feb 2 '12 at 11:41
add comment

2 Answers

up vote 4 down vote accepted

If a telescoping sum starts at $n=m$, then $$ \sum_{n=m}^{N}\left( a_{n}-a_{n+1}\right) =a_{m}-a_{N+1} $$

and the telescoping series is thus $$ \begin{eqnarray*} \sum_{n=m}^{\infty }\left( a_{n}-a_{n+1}\right) &=&\lim_{N\rightarrow \infty }\sum_{n=m}^{N}\left( a_{n}-a_{n+1}\right) \\ &=&a_{m}-\lim_{N\rightarrow \infty }a_{N+1}=a_{m}-\lim_{N\rightarrow \infty }a_{N+1} \\ &=&a_{m}-\lim_{N\rightarrow \infty }a_{N}. \end{eqnarray*} $$

Of course the series converges if and only if there exists $\lim_{N\rightarrow \infty }a_{N}.$

The case $m=1$ is $$ \begin{eqnarray*} \sum_{n=1}^{N}\left( a_{n}-a_{n+1}\right) &=&a_{1}-a_{N+1} \\ \sum_{n=1}^{\infty }\left( a_{n}-a_{n+1}\right) &=&a_{1}-\lim_{N\rightarrow \infty }a_{N}. \end{eqnarray*} $$ The difficult part is to write a series $ \sum_{n=m}^{\infty}u_n$ in the form $ \sum_{n=m}^{\infty}\left( a_{n}-a_{n+1}\right)$, when possible. Concerning Wilf-Zeilberger method (also called "creative telescoping") see answers to the question Mathematical Telescoping.

Example: write $\frac{2n+1}{n^{2}\left( n+1\right) ^{2}}=\frac{1}{n^{2}}- \frac{1}{\left( n+1\right) ^{2}}$ to evaluate $$ \begin{eqnarray*} \sum_{n=1}^{\infty }\frac{2n+1}{n^{2}\left( n+1\right) ^{2}} &=&\sum_{n=1}^{\infty }\left( \frac{1}{n^{2}}-\frac{1}{\left( n+1\right) ^{2} }\right) \\ &=&1-\lim_{N\rightarrow \infty }\frac{1}{N^{2}}=1-0=1. \end{eqnarray*} $$

Added in response to the edited question. The standard technique is to expand $\frac{4}{(n+1)(n+2)}$ into partial fractions. Write $$ \begin{eqnarray*} \frac{4}{(n+1)(n+2)} &=&\frac{A}{n+1}+\frac{B}{n+2} \\ &=&\frac{(n+2)A+(n+1)B}{(n+1)(n+2)} \\ &=&\frac{\left( A+B\right) n+2A+B}{(n+1)(n+2)} \end{eqnarray*} $$

and find the constants $A$ and $B$. The following system must hold $$ \left\{ \begin{array}{c} A+B=0 \\ 2A+B=4 \end{array} \right. \Leftrightarrow \left\{ \begin{array}{c} A=4 \\ B=-4. \end{array} \right. $$

So $$ \frac{4}{(n+1)(n+2)}=\frac{4}{n+1}-\frac{4}{n+2} $$

and, since $a_{n}=\frac{4}{n+1}$, you get $$ \begin{eqnarray*} \sum_{n=1}^{\infty }\frac{4}{(n+1)(n+2)} &=&\sum_{n=1}^{\infty }\left( \frac{ 4}{n+1}-\frac{4}{n+2}\right) \\ &=&\frac{4}{1+1}-\lim_{n\rightarrow \infty }\frac{4}{n+1} \\ &=&2-0=2. \end{eqnarray*} $$

share|improve this answer
    
thanks for your answer but I think I'm miss understand some steps and the problem is that I only have left 3 hours to the exam. So I've updated my question with a specific example. A step-by-step example would be really much appreciated thanks –  Totty Feb 2 '12 at 14:22
    
@Totty: Do you need additional details? –  Américo Tavares Feb 2 '12 at 16:36
    
no, that was ok. thanks :D –  Totty Feb 10 '12 at 9:13
add comment

To add to Américo Tavares's answer, for more general telescoping series:

$$ \sum_{n=m}^{N}\left( a_{n}-a_{n+k}\right) =(a_{m}+a_{m+1}+\cdots+a_{m+k-1})-(a_{N+1}+a_{N+2}+\cdots+a_{N+k}) $$

$$ \begin{eqnarray*} \sum_{n=m}^{\infty }\left( a_{n}-a_{n+k}\right) &=&\lim_{N\rightarrow \infty }\sum_{n=m}^{N}\left( a_{n}-a_{n+k}\right) \\ &=&\lim_{N\rightarrow \infty }((a_{m}+a_{m+1}+\cdots+a_{m+k-1})-(a_{N+1}+a_{N+2}+\cdots+a_{N+k}))\\ &=&(a_{m}+a_{m+1}+\cdots+a_{m+k-1})-\lim_{N\rightarrow \infty }(a_{N+1}+a_{N+2}+\cdots+a_{N+k})\\ &=& a_{m}+a_{m+1}+\cdots+a_{m+k-1}-k\lim_{N\rightarrow\infty}a_N. \end{eqnarray*} $$

share|improve this answer
    
I think that if the series is convergent it evaluates to $$ \sum_{m=1}^{\infty }\left( a_{n}-a_{n+k}\right) =a_{m}+a_{m+1}+\ldots +a_{m+k-1}-k\lim_{N\rightarrow \infty }a_{N}. $$ –  Américo Tavares Feb 2 '12 at 12:45
    
Ah, in fact you're correct - editing to make the correction. Thanks! (I should know better than to try to do math at 6a!) –  Aru Ray Feb 2 '12 at 13:42
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.